Vandermonde determinantal ideals - Watanabe, Junzo; Yanagawa, Kohji (Mathematica Scandinavica, 2019)
We show that the ideal generated by maximal minors (i.e., k+1-minors) of a (k+1) × n Vandermonde matrix is radical and Cohen-Macaulay. Note that this ideal is generated by all Specht polynomials with shape (n-k,1, …,1).